The Virgin Birth of Jesus in the Talmudic Context: A Philological and Historical Analysis - Jaffé, Dan (Laval théologique et philosophique)

(untitled) (Faculté de philosophie, Université Laval, 2012)
This article proposes a philological and historic analysis of the Talmudic name Ben Pantera. It is suggested that this ancient expression has to be understood as corresponding to a period in which the Jews wished to think of Christianity, choosing the person of Jesus as an emblematic figure of this reality. The expression Ben Pantera expresses mockery and even scorn towards Jesus. It must be placed back in a period in which, on account of the doctrinal controversies between Jews and Christians, the two religions had consummated a Parting of the Ways and acknowledged each other as rivals. Thus, Ben Pantera appears to be the oldest mention of Jesus in the Talmudic literature.